Systemic osteoprotegerin does not improve peri‐implant bone volume or osseointegration in rabbits - Choi, Joseph H.; Wang, Zhiwei; Ross, Frederick P.; Meulen, Marjolein C. H.; Bostrom, Mathias P. G. (Journal of orthopaedic research, 2021)
Anti‐RANKL (receptor activator of nuclear factor kappa‐B ligand) agents function by blocking the differentiation of osteoclasts, thereby proving useful in the clinical management of postmenopausal osteoporosis. The effects of such agents on osseointegration is less well understood. The purpose of the current study was to investigate whether osteoprotegerin (OPG), an osteoclast inhibitor, enhances the known anabolic effects of mechanical loading (VEH) and intermittent PTH (iPTH) using a well‐established rabbit model of osseointegration. In the first set of experiments, OPG was administered either alone or combined with iPTH to study its effects on measured bone mass. The second set of experiments was conducted using a higher dosage of OPG (10 mg/kg) to explore its early impact at the cellular and molecular levels. All subjects had mechanical load applied to the implant on one extremity, and no load applied on the contralateral side. In the first set of experiments, OPG alone decreased peri‐implant bone mass compared to the mechanical loading group, whereas OPG + iPTH increased peri‐implant bone mass compared to the OPG group. In the second set of experiments, high‐dose OPG significantly decreased osteoclast number (−74.3%) at 1 week. However, this effect was not sustained as osteoclast number returned to baseline by 2 weeks. These results suggest that systemic administration of OPG does not enhance osseointegration, but rather has a detrimental effect.